Financial conflicts of interest and their association with outcome and quality of fibromyalgia drug therapy randomized controlled trials. (27th May 2015) - Pang, Winnie K.; Yeter, Karen C.; Torralba, Karina D.; Spencer, Horace J.; Khan, Nasim A.
Abstract: Aims: To evaluate the association of financial conflicts of interest (FCOI) with the characteristics, outcome and reported methodological quality of fibromyalgia drug therapy randomized controlled trials (FM‐RCTs). Methods: A cross‐sectional study of original, parallel‐group, drug therapy FM‐RCTs published between 1997 and 2011 from Medline and Cochrane Central Register of Controlled Trials was conducted. Two reviewers independently assessed each RCT for funding source, authors' FCOI(s), study characteristics, reporting of methodological measures important for internal validity and outcome (positive [statistically significant result favoring experimental drug for the primary outcome] or non‐positive). Results: Forty‐seven RCTs were eligible with funding source as: 26 (55.3%) industry; eight (17%) non‐profit source(s); five (10.6%) mixed; and eight (17%) unspecified. Industry‐funded RCTs were more likely to be multicenter and enroll greater number of patients. Reporting of key methodological measures was suboptimal; however, industry and non‐profit funded RCTs did not differ in their reporting. Thirty (63.8%) RCTs had ≥ one author who disclosed an FCOI (receipt of research grant [21, 44.7%], industry sponsor employee [20, 42.6%], receipt of consultancy fee/honorarium [16, 34%] and stock ownership [11, 23.4%]). Although industry funding and certain authors' FCOIs (employment and receipt of consultancy fee/honorarium) were univariately associated with positive outcome, such association was not observed after adjusting for study sample size. Conclusions: The majority of FM‐RCTs were industry‐sponsored, and had at least one author with an FCOI. Reporting of key methodological measures was suboptimal. After adjusting for study sample size, no association of industry funding or author's FCOI with study outcome was seen.